Loci as Subject of Derision: Between Cicero’s Rhetorical Theory and Practice - Kučinskienė, Audronė (Literatūra, 2022)
There is no doubt that commonplaces, so called topoi, or loci, played a very important role both in the ancient rhetorical theory and in practice. They conform to the main part of invention in the rhetorical treatises, such as Rhetorica ad Herennium, Cicero’s De Inventione, Topica etc., and they enable an orator to develop his argument in any desirable direction (in utramque partem), and sometimes become the main tool of rhetorical strategy. In his Orator, Cicero claims, that an accomplished speaker, whom he tries to delineate as an ideal, will be perfectly familiar with commonplaces and be able to treat them critically and manipulate according to his purposes. In this paper, on the ground Cicero’s Verrine speeches, I shall analyze how the orator predicts his opponents’ topoi and presents them in a different light, and by criticizing or even by mocking them, he diminishes them in order to strengthen his own arguments. In some cases, e.g. in the Fifth Book of the Actio secunda in Verrem (Verr. 2.5), this becomes the main strategy of speech, and corresponds to the methods delineated in the Orator 49.